Assessing common birds' ecological requirements to address nature conservation in permanent crops: Lessons from Italian vineyards. (15th April 2017) - Assandri, Giacomo; Bogliani, Giuseppe; Pedrini, Paolo; Brambilla, Mattia
Abstract: Viticulture has contributed to shaping cultural landscapes in several regions across all continents. Recent farming intensification is causing landscape homogenization and biodiversity loss in several of those areas, but knowledge about the impacts on biodiversity in vineyards is still scarce. Simplified agro-ecosystems resulting from intensification host mainly generalist and common species, which still play a key role in the regulation of ecosystems and in the provision of ecosystem services. We assessed the abundance of 11 common bird species at 47 linear transects in a vineyard-dominated landscape in Trentino (NE Italy), in both spring and winter, and analysed abundance variation in relation to three independent groups of predictors: landscape, management, and topographic-climatic variables. In the majority of species (7), abundance was primarily or considerably affected by landscape attributes. However, an additional 5 species were largely affected by management practices, often with conspicuous seasonal differences. Overall, landscape and management heterogeneity positively affected the abundance of 6 species. Vineyard cover (and in particular the new spalliera trellising system) was negatively related with the abundance of 6 species, with the strongest impacts occurring in winter. On the contrary, the cover of marginal habitats had major positive effects over 8 species. Hedgerows, tree rows, and dry stone walls, as well as traditional pergola vineyards and landscape and management heterogeneity should be conserved or restored in viticultural landscapes to promote the abundance of common bird species. This strategy would ensure the maintenance of the ecosystem services they provide, while promoting the general sustainability of the agroecosystem. Highlights: Vineyard cover reduces the abundance of several common bird species. The negative effect of vineyards on common birds is particularly striking in winter. Landscape and management heterogeneity promote the abundance of most common birds. Marginal habitats and traditional elements enhance the abundance of common species.